Pengaruh Struktur Modal Dalam Memoderasi Struktur Aktiva, Ukuran Perusahaan, Risiko Bisnis Terhadap Nilai Perusahaan - Ramadhani, Suci; Permata, Lukita Tri; Putri, Andini Utari (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the effect of asset structure, firm size, and business risk on firm value, with capital structure as a moderating variable. The research focuses on automotive and components subsector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023, using a descriptive quantitative approach. The data utilized consists of annual financial reports analyzed using moderation regression methods. The findings reveal that asset structure and firm size do not have a significant effect on firm value. Conversely, business risk has a significant negative effect on firm value. Capital structure fails to moderate the relationship between firm size and firm value. Collectively, the influence of the independent variables on firm value is entirely significant. This study has important implications for company management in enhancing asset management efficiency, transparency in managing business risks, and optimizing capital structure. For investors, the findings emphasize the importance of evaluating business risks and capital structure in investment decision-making. Future researchers are recommended to incorporate external factors such as macroeconomic conditions or regulations, as well as additional variables like profitability or liquidity, for a more comprehensive analysis